2016
DOI: 10.12669/pjms.326.10849
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia in jaundiced neonates receiving phototherapy

Abstract: Objective:To determine the frequency of hypocalcemia in term neonates with jaundice receiving phototherapy.Methods:This was a cross sectional study conducted at Neonatal intensive care unit, National Institute of Child Health, Karachi from 1st January 2014 to 30th December 2014. A total of 123 term neonates with jaundice of either gender managed by phototherapy were enrolled in the study. Gestational age was assessed through modified Ballard scoring. Duration of phototherapy was recorded. A sample of 3 ml of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 11 publications
3
19
1
1
Order By: Relevance
“…This finding was in agreement with studies in Pakistan and Iran that reported neonates developed hypocalcemia after receiving phototherapy as a treatment for neonatal jaundice. 24 , 25 It is similar to an Egyptian which found that hypocalcemia was a complication of phototherapy in newborns. 26 Also, there is a statistically significant association between preterm and low level of serum vitamin D, which is in contrast with a study conducted in Turkey which reported that preterm was associated with hypocalcemia, not with vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 53%
“…This finding was in agreement with studies in Pakistan and Iran that reported neonates developed hypocalcemia after receiving phototherapy as a treatment for neonatal jaundice. 24 , 25 It is similar to an Egyptian which found that hypocalcemia was a complication of phototherapy in newborns. 26 Also, there is a statistically significant association between preterm and low level of serum vitamin D, which is in contrast with a study conducted in Turkey which reported that preterm was associated with hypocalcemia, not with vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 53%
“…Although considered safe, the biological properties of BR photoisomers and their oxidation products have not properly been investigated. However, the still scarce data obtained until now suggests some biological activity of these products ( Jašprová et al, 2018 ), which may account for the reported clinical observations ( Raghavan et al, 2005 ; Xiong et al, 2011 ; Mcnamee et al, 2012 ; Arnold et al, 2014 ; Khan et al, 2016 ; Auger et al, 2019 ; Safar and Elsary, 2020 ). In addition, practically no mechanistic studies have been performed to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the metabolism of BR photoisomers seems to have clinical importance. Although PT is an effective, non-invasive, and relatively safe therapeutic method, accompanying potential side effects of the treatment are known in clinical practice, including: hypocalcemia ( Khan et al, 2016 ), dehydration ( Xiong et al, 2011 ), ileus ( Raghavan et al, 2005 ), type 1 diabetes ( Mcnamee et al, 2012 ), allergies ( Safar and Elsary, 2020 ), increased incidence of cancer at advanced age ( Auger et al, 2019 ), and even increased mortality of extremely low birth-weight infants ( Arnold et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the development of hypocalcemia driven by phototherapy remains unclear, but it may be associated with increased excretion of calcium in the urine during phototherapy. It may also be caused by light passing through the skull, which exerts an inhibitory effect on the pineal gland, thus leading to decreased melatonin secretion, which in turn leads to a decrease in cortisol secretion, thus enhancing the absorption of calcium by bone tissue and causing a decrease in blood calcium levels ( 62 , 63 ). Therefore, it has been hypothesized that hypocalcemia may be alleviated by wearing protective headgear during phototherapy ( 64 , 65 ).…”
Section: Adverse Reactions Of Phototherapy For Neonatal Hyperbilirmentioning
confidence: 99%